2003
DOI: 10.1007/s00702-003-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Specific modulation of sigma binding sites by the anxiolytic drug opipramol

Abstract: The atypical anxiolytic and antidepressive drug opipramol binds with high affinity to sigma1 and somewhat lower affinity to sigma2 sites. After subchronic treatment, opipramol significantly down-regulated sigma2 but not sigma1 sites. This effect was not seen for imipramine, citalopram, and reboxetine under similar conditions. On the other hand, only imipramine reduced the number of sigma1 sites. It is suggested that effects at sigma2 sites are involved in the anxiolytic properties of opipramol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…With opipramol no dose-dependency became apparent between 10, 20 and 40 mg/kg. In a modified design of the forced swim test (9 days of treatment) we also observed a reduced immobility time for 20 mg/kg opipramol daily, but the effect was less pronounced than following a comparable treatment with the antidepressants reboxetine or citalopram [15]. The relationship between in vitro IC50 values (half-maximum inhibitor concentrations) for sigma binding (nmol/l) and ex vivo ED50 values (oral doses which occupy sigma sites by 50 % one hour after administration) (mg/kg body weight) for opipramol and some other sigma ligands.…”
Section: Data Indicative Of An Antidepressant-like Potential For Opipmentioning
confidence: 68%
See 1 more Smart Citation
“…With opipramol no dose-dependency became apparent between 10, 20 and 40 mg/kg. In a modified design of the forced swim test (9 days of treatment) we also observed a reduced immobility time for 20 mg/kg opipramol daily, but the effect was less pronounced than following a comparable treatment with the antidepressants reboxetine or citalopram [15]. The relationship between in vitro IC50 values (half-maximum inhibitor concentrations) for sigma binding (nmol/l) and ex vivo ED50 values (oral doses which occupy sigma sites by 50 % one hour after administration) (mg/kg body weight) for opipramol and some other sigma ligands.…”
Section: Data Indicative Of An Antidepressant-like Potential For Opipmentioning
confidence: 68%
“…Imipramine, in contrast, caused no reduction of sigma tot or sigma 2 receptor densities, but a weak reduction of sigma 1 receptor densities by 16 % compared to control. Neither of the treatment led to any relevant change in the affinities of either radioligand [15].…”
Section: Data Indicative For In Vivo Sigma Bindingmentioning
confidence: 86%
“…We used 3 Sigma‐1 ligands, AC915 (N‐(2‐(3,4‐dichlorophenyl)acetoxy)‐ethylpyrrolidine (specific Sigma‐1 antagonist),32 haloperidol (Sigma‐1 antagonist),33 and opipramol (specific Sigma‐1 agonist)34 to determine whether these small molecules can mimic the effect of altered expression of SIGMAR1 on TDP‐43 subcellular localization (see Fig 4D). We observed that both AC915 and opipramol had a significant effect on TDP‐43 localization, whereby 50nM of AC915 (antagonist) or 15nM of opipramol (agonist) significantly decreased (1.5‐fold, p = 0.038) or increased (1.5‐fold, p = 0.020), respectively, the relative level of TDP‐43 in the cytoplasm compared with untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Opipramol is a high-affinity Sig-1R agonist with weak affinities for H 1 , sigma-2, 5-HT 2 , and D 2 receptors. Opipramol lacks affinities for serotonin and noradrenalin reuptake sites[99]. Opipramol is effective in treatment of depressive mood, somatization, anxiety, and sleep disturbance[100].…”
Section: Case Reports Clinical Trials and Brain Imaging Studies mentioning
confidence: 99%